An investigation into the impact of career guidance on career choice of secondary students in Botswana: career guidance - oats, reginald; Rukewe, Yewande (Advances in Social Sciences Research Journal, 2020)
This is a qualitative study undertaken through a case study design. The study was carried out to investigate into the impact of career guidance on career choice of secondary students in Botswana. Data was collected from form 5 students, guidance & counselling teachers and principals at four (4) private senior secondary schools in Gaborone using a focus group interview, individual interviews and a qualitative-questionnaire. The study was inspired by the quest to understand the impact of career guidance and information provided in secondary in determining career choice of students in schools. The Systems Theory Framework (STF) was used as a guide the study. The findings reveal the absence of a robust career guidance programmes and practices in most of the schools. In schools with career guidance programmes, these were found wanting. Students show their awareness on subject combination and requirements for entry into higher institution in their responses. However, majority of the participants did not have enough career information as expected of students at their final stage of secondary education. The study concludes that due to the dynamic nature of career choice and planning process, career decision of students are influenced by various factors and that as such students need career guidance and information in order to make informed and wise decisions. Thus, in light of findings from this study we recommend that systematic guidance programmes which will adequately address the career needs of learners be developed and provided in schools.